Necrosis Driven Triglyceride Synthesis Primes Macrophages for Inflammation During Mycobacterium tuberculosis Infection - Jaisinghani, Neetika; Dawa, Stanzin; Singh, Kaurab; Nandy, Ananya; Menon, Dilip; Bhandari, Purva Deepak; Khare, Garima; Tyagi, Anil; Gandotra, Sheetal (Frontiers in Immunology, 2018)
Pulmonary tuberculosis exhibits granulomatous inflammation, a site of controlling bacterial dissemination at the cost of host tissue damage. Intrigued by the granuloma type dependent expression of inflammatory markers in TB, we sought to investigate underlying metabolic changes that drive amplification of inflammation in tuberculosis. Here we show an association of higher inflammation in necrotic granulomas with the presence of triglyceride rich foamy macrophages. The conspicuous absence of these macrophages in solid granulomas identified a link between the ensuing pathology and the metabolic programming of foamy macrophages. Consistent with in vivo findings, in vitro infection of macrophages with Mycobacterium tuberculosis (Mtb) led to increase in triglyceride synthesis only under conditions of ~60% necrosis. Genetic and pharmacologic intervention that reduced necrosis prevented this bystander response. We further demonstrate that necrosis independent of Mtb also elicits the same bystander response in human macrophages. We identified a role for the human enzyme involved in triglyceride synthesis, diacylglycerol O-acyltransferase (DGAT1), in this phenomenon. The increased TG levels in necrosis associated foamy macrophages promoted the pro-inflammatory state of macrophages to infection while silencing expression of diacylglycerol O-acyltransferase (DGAT1) suppressed expression of pro-inflammatory genes. Our data thus invoke a role for storage lipids in the heightened host inflammatory response during infection associated necrosis. Our data provide a functional role to macrophage lipid droplets in host defense and open new avenues for developing host directed therapies against tuberculosis.